2015
DOI: 10.1038/srep14543
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in advanced HIV disease and late presentation according to European consensus definitions

Abstract: Effectiveness of highly active antiretroviral therapy is limited for a large proportion of individuals living with HIV presenting for medical care at an advanced stage. Controversial results of gender differences in risk of late HIV diagnosis were reported among existing literatures. Therefore, we conducted this meta-analysis to synthesize a summary of gender differences in risk of advanced HIV disease (AHD) and late presentation (LP) according to European consensus definitions. Totally, 32 studies were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
19
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 58 publications
7
19
1
Order By: Relevance
“…Despite evidence of earlier diagnosis, people who had ever injected drugs were more likely to delay presentation in our study and less likely to be engaged in later steps of the cascade in another analysis of the OCS . In contrast to findings from a recent meta‐analysis of 32 studies world‐wide , we identified a higher prevalence of late diagnosis and presentation among females. This difference may be attributable to variations in the epidemic across populations and geographies .…”
Section: Discussioncontrasting
confidence: 99%
“…Despite evidence of earlier diagnosis, people who had ever injected drugs were more likely to delay presentation in our study and less likely to be engaged in later steps of the cascade in another analysis of the OCS . In contrast to findings from a recent meta‐analysis of 32 studies world‐wide , we identified a higher prevalence of late diagnosis and presentation among females. This difference may be attributable to variations in the epidemic across populations and geographies .…”
Section: Discussioncontrasting
confidence: 99%
“…With this background, one study from China indicated that male patients were 1.73 times more likely to present with advanced HIV diagnosis than female patients [31], similar to a study from Nigeria, where male patients were 1.8 times more likely to present with advanced HIV diagnosis [32]. Also another study assessing mortality in Uganda had indicated that male patients were more severely ill with most of WHO clinical stages 3 and 4 AIDS-defining illnesses (36% versus 33%, p < 0.0001) and they had 37% more risk of death compared to female patients on receipt of ART (OR = 1.37, p < 0.001) [12].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a few limitations should be noted. First, high heterogeneity was shown in overall and subgroup analyses, which might add some uncertainty about the magnitude of the conclusion [ 45 , 46 ], and should be taken into consideration when interpreted the results. Second, all the included studies were published in English or Chinese, possibly leading to a language bias, although some previous studies suggested that it did not appear to influence the results [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, there is a concern regarding the potential risk bias. All included studies were retrospective studies, and the integrity of original data and potential recall bias might affect the results [ 45 ]. Fourth, the included studies were small-scale case control studies with small sample size, which might lower the precision of the results.…”
Section: Discussionmentioning
confidence: 99%